2006
DOI: 10.1038/sj.bjp.0706779
|View full text |Cite
|
Sign up to set email alerts
|

Role of reactive oxygen species and gp91phox in endothelial dysfunction of pulmonary arteries induced by chronic hypoxia

Abstract: 1 This study investigates the role of nitric oxide (NO) and reactive oxygen species (ROS) on endothelial function of pulmonary arteries in a mice model of hypoxia-induced pulmonary hypertension. 2 In pulmonary arteries from control mice, the NO-synthase inhibitor N o -nitro-L-arginine methyl ester (L-NAME) potentiated contraction to prostaglandin F 2a (PGF 2a ) and completely abolished relaxation to acetylcholine. In extrapulmonary but not intrapulmonary arteries, acetylcholine-induced relaxation was slightly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
101
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(115 citation statements)
references
References 49 publications
12
101
0
2
Order By: Relevance
“…In keeping with our present findings in neonatal rats, excessive production of O 2 •Ϫ has been previously implicated in hypoxia-induced inhibition of both endothelium-dependent (22) and -independent (47) pulmonary arterial relaxation in adult animals. While O 2 •Ϫ is not itself a highly reactive oxidant (57), it reacts very efficiently with NO to produce peroxynitrite anion, a ROS that is a major oxidizing and nitrating agent (2).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In keeping with our present findings in neonatal rats, excessive production of O 2 •Ϫ has been previously implicated in hypoxia-induced inhibition of both endothelium-dependent (22) and -independent (47) pulmonary arterial relaxation in adult animals. While O 2 •Ϫ is not itself a highly reactive oxidant (57), it reacts very efficiently with NO to produce peroxynitrite anion, a ROS that is a major oxidizing and nitrating agent (2).…”
Section: Discussionsupporting
confidence: 80%
“…Pulmonary vascular ROS were detected in situ utilizing DHE, a dye that fluoresces upon reaction with ROS [predominantly O2 •Ϫ but also H2O2 and hydroxyl radicals (50)], using a method recently described by others (22,24). Briefly, the lungs of two animals per group and time point were snap frozen in Tissue-Tek OCT, as previously described (28), and stored at Ϫ80°C.…”
Section: Methodsmentioning
confidence: 99%
“…Taking together, these studies suggest that gp91 phox has different functions in cardiac remodeling depending on the nature of cardiac damage. In addition to the heart, it has also been reported that in intrapulmonary arteries, endothelial dysfunction induced by chronic hypoxia depends on gp91 phox (45).…”
Section: Discussionmentioning
confidence: 99%
“…In a mouse model of chronic hypoxia-induced pulmonary arterial hypertension, we have shown that the relaxant response induced by the β 2 -AR stimulation, which is also endothelium-and eNOSdependent, is preserved, whereas the relaxant response to acetylcholine is decreased [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…As in other cardiovascular diseases, endothelial dysfunction in models of pulmonary arterial hypertension is established when pulmonary arteries exhibit a decrease in the relaxant response to acetylcholine, the reference endothelium-dependent vasodilator, acting through the activation of endothelial muscarinic receptors coupled to NO production [4,5]. In a mouse model of chronic hypoxia-induced pulmonary arterial hypertension, we have shown that the relaxant response induced by the β 2 -AR stimulation, which is also endothelium-and eNOSdependent, is preserved, whereas the relaxant response to acetylcholine is decreased [5,6].…”
Section: Introductionmentioning
confidence: 99%